Structural design and integral assembly procedure of rigid-flexible tensegrity airship structure. (1st June 2023) - Li, Shiping; Hu, Jianhui; Chen, Longlong; Zhang, Yibei; Mi, Xiang; Huang, Xiaohui; Chen, Wujun
Abstract: A rigid-flexible tensegrity airship structure is proposed through the systematic research and design of the wheel spoke–shaped stiffening ring, carbon fiber–reinforced polymer slender cable, central longitudinal compression truss, and spherical multi-part integration assemblage. This structure aimed to fully utilize the structural performance advantages of a semi-rigid airship and the self-equilibrating characteristics of a tensegrity structure. The design of the spherical multi-part integration assemblage facilitates the rotation of a wheel spoke–shaped stiffening ring and enhances the installation efficiency of longitudinal cables. The tensegrity system is applied to the rigid-flexible integrated airship structure to make the main compression-bearing shaft bear the compressive stress and the longitudinal cables bear the tensile stress, thereby creating a rigid-flexible tensegrity airship structure with the self-equilibrating system. The feasibility of the structural design, component preparation, and integrated assembly technology of the rigid-flexible tensegrity airship has been effectively verified and evaluated by the integral assembly procedure, which ensures the assembly safety and reliability of the airship structure. The rigid-flexible tensegrity airship structure exhibits a clear load transfer path, high stiffness, bearing capacity, and strong shape retention capacity under low pressure conditions, which provides an ideal structural form for the stratospheric airship. Highlights: A new modular large-scale CFRP wheel spoke–shaped stiffening ring is proposed. A CFRP slender cable with a geometric locking end-fitting is designed and developed. A new type of spherical multi-part integration assemblage is designed to facilitate the installation of longitudinal cables. Two types of large-span central longitudinal compression trusses are designed and developed. The tensegrity system is applied to create a rigid-flexible tensegrity airship structure.